2019
DOI: 10.1101/582338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intrinsic Disorder and Degeneracy in Molecular Scale Organization of Biological Membrane

Abstract: The scale-rich spatiotemporal organization in biological membrane dictates the "molecular encounter" and in turn the larger scale biological processes such as molecular transport, trafficking and cellular signalling. In this work, we explore the degeneracy in lateral organization in lipid bilayer systems from the perspective of energy landscape theory. Our analysis on molecular trajectories show that bilayers with lipids having in-vivo characteristics have a highly frustrated energy landscape as opposed to a f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…We recently showed that χ 2 works as a high-fidelity marker between the liquid order (L o ) and liquid disordered (L d ) regions in the membrane system at molecular length scales. 31,50,51 χ 2 was originally applied on the granular material by Falk and Langer 49 and is given as…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently showed that χ 2 works as a high-fidelity marker between the liquid order (L o ) and liquid disordered (L d ) regions in the membrane system at molecular length scales. 31,50,51 χ 2 was originally applied on the granular material by Falk and Langer 49 and is given as…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Lipids in the L d phase have higher χ 2 values than lipids in the L o phase. 31,50 Detecting Boundaries Using SVM. Identifying molecules at the phase boundaries and measuring the atomic scale motions to quantify the interfacial properties is a challenge in experimental and computational science.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides these commonly used markers, we also use the degree of non-affine displacements (χ 2 ) [49] to distinguish between the different phases in the lipid bilayer systems. We recently showed that χ 2 works as a high-fidelity marker between the liquid order (L o ) and liquid disordered (L d ) regions in the membrane system at molecular length scales [31,50,51]. χ 2 was originally applied on granular material by Falk and Langer ( [49]) and is given as:…”
Section: Order Parameters Used As Domain Boundary Classifiersmentioning
confidence: 99%
“…The energy at the domain boundary is given by the product of line tension and boundary length. Line tension can be tuned based on the chemical composition of the lipid mixture, which manifests as differential molecular interactions [16,[29][30][31][32] and external factors such as temperature that effect distributions at the interface.…”
Section: Introductionmentioning
confidence: 99%